Imaging of brain tumors with histological correlations - Drevelegas, Antonios 1947- (Heidelberg, Germany Springer Berlin, 2010)
This volume provides a deeper understanding of the diagnosis of brain tumors by correlating radiographic imaging features with the underlying pathological abnormalities. All modern imaging modalities are used to complete a diagnostic overview of brain tumors with emphasis on recent advances in diagnostic neuroradiology. High-quality illustrations depicting common and uncommon imaging characteristics of a wide range of brain tumors are presented and analysed, drawing attention to the ways in which these characteristics reflect different aspects of pathology. Important theoretical considerations.
Epidemiology, histologic classification, and clinical course of brain tumors -- Imaging modalities in brain tumors -- Molecular abnormalities in gliomas -- The clinical applicability of fMRI and DTI in patients with brain tumors -- Low-grade gliomas -- High-grade gliomas -- Pineal tumors -- Embryonal tumors -- Tumors of the cranial nerves -- Meningeal tumors -- Central nervous lymphomas and hemopoietic neoplasms -- Masses of the sellar and junxtasellar region -- Brain metastasis -- Scintigraphy for brain tumors.
Electronic reproduction.
Keywords: Brain -- Tumors -- Diagnosis; Brain -- Tumors -- Histopathology